2021
DOI: 10.3390/ijms22169025
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Interactions between Calmodulin and a Mutant Huntingtin Model Might Reduce the Cytotoxic Level of Intracellular Ca2+: A Molecular Dynamics Study

Abstract: Mutant huntingtin (m-HTT) proteins and calmodulin (CaM) co-localize in the cerebral cortex with significant effects on the intracellular calcium levels by altering the specific calcium-mediated signals. Furthermore, the mutant huntingtin proteins show great affinity for CaM that can lead to a further stabilization of the mutant huntingtin aggregates. In this context, the present study focuses on describing the interactions between CaM and two huntingtin mutants from a biophysical point of view, by using classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Abnormal protein–protein interactions are associated with various diseases such as cancers and neurodegenerative diseases. , Targeting the abnormal protein–protein interactions and thereby normalizing protein function are important strategies for developing therapeutics to treat diseases. Previous studies in our lab and others have identified an abnormal protein–protein interaction between mHTT and calmodulin (CaM). mHTT from HD patients bound to CaM with higher affinity compared to wild-type HTT from postmortem brain tissue . Studies conducted in our lab found that CaM is present in intranuclear inclusions and co-localizes with HTT, transglutaminase, and transglutaminase-induced cross-links within the nucleus of postmortem cortical tissue from HD patients .…”
Section: Introductionmentioning
confidence: 66%
“…Abnormal protein–protein interactions are associated with various diseases such as cancers and neurodegenerative diseases. , Targeting the abnormal protein–protein interactions and thereby normalizing protein function are important strategies for developing therapeutics to treat diseases. Previous studies in our lab and others have identified an abnormal protein–protein interaction between mHTT and calmodulin (CaM). mHTT from HD patients bound to CaM with higher affinity compared to wild-type HTT from postmortem brain tissue . Studies conducted in our lab found that CaM is present in intranuclear inclusions and co-localizes with HTT, transglutaminase, and transglutaminase-induced cross-links within the nucleus of postmortem cortical tissue from HD patients .…”
Section: Introductionmentioning
confidence: 66%
“…Protein-protein interaction (PPI) between calmodulin and mutant huntingtin protein has been shown to contribute to the progression of Huntington's disease (HD). 66,67 Using the high-throughput AlphaScreen platform, Klus et al 68 discovered a series of sultams (Fig. 26) as potent smallmolecule PPI disruptors.…”
Section: Treatment Of Huntington's Diseasementioning
confidence: 99%
“…The study proposes a threshold of nine proline residues for significant helical disruption rates and emphasizes the need for further dynamic investigations to understand the interactions of these novel mutant models with other cellular counterparts. A year later, the authors built on their previous work [ 257 ] by further exploring the interactions between mHTT models and calmodulin (CaM) [ 258 ]. This time, the authors investigated how their previously developed mHTT models, especially those with key-point mutations (such as the 9P(EM)), interact with CaM.…”
Section: Polyq Accumulation Behavior and Theoretical Modelsmentioning
confidence: 99%
“…This time, the authors investigated how their previously developed mHTT models, especially those with key-point mutations (such as the 9P(EM)), interact with CaM. The findings suggest that these mutant models show different binding affinities, total interaction energies and induce distinct structural changes within CaM’s structure [ 258 ]. Consequently, this research enhances our understanding of mHTT–CaM complexes and their implications in HD, offering insights into potential therapeutic strategies targeting these interactions.…”
Section: Polyq Accumulation Behavior and Theoretical Modelsmentioning
confidence: 99%
See 1 more Smart Citation